Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Usaha Jasa Salon Di Kota Ambon - Join Rachel Luturmas (P3M Politeknik Negeri Ambon, 2023)
This study aims to examine the effect of service quality on customer satisfaction and customer loyalty as well as the effect of customer satisfaction on customer loyalty. The development of the Salon Service Industry in Ambon city has increased competition for salon services. Heterogeneous customers, workers who already have experience and high competence move, usually the salon customers also move. Service providers must recruit new people who are not necessarily quickly accepted by customers. Besides the lack of participation in seminars, courses, and exhibitions related to the salon business in order to follow development trends and increase expertise. Respondents in this study were salon customers at middle to upper-class salons in Ambon City, with a total of 150 respondents. The analysis used in testing data quality is validity and reliability analysis. Hypothesis testing is done using multiple regression analysis The regression test results show that service quality has a positive effect on customer loyalty as well as customer satisfaction has a positive effect on customer loyalty. Â Keywords: Service Quality, Customer Satisfaction, Customer Loyalty